2022
DOI: 10.1002/hec.4466
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a hypertension diagnosis on health behaviors: A two‐dimensional regression discontinuity analysis

Abstract: This paper explores how a diagnosis of hypertension might affect a person's health‐related behaviors. The analysis uses a two‐dimensional regression discontinuity design because hypertension is diagnosed when a person's systolic or diastolic blood pressure (SBP or DBP) surpasses a pre‐established threshold. We find that those closely above the SBP threshold significantly adjusted their lifestyle, such as reducing daily fat intake and quitting smoking, while those just surpassing the DBP cutoff did not. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 41 publications
(58 reference statements)
1
16
0
Order By: Relevance
“…The density plots for diastolic BP, systolic BP, and the BPS are reported in Fig 1 . The graphical inspection of these plots confirmed the absence of manipulation around the respective cutoffs, since the density curve runs smoothly through the cutoff (if a manipulation had occurred, we would have seen a jump in the distribution of these variables close to the cutoff). The same result applies to the density plots for the reduced sample for the analysis of the secondary 18) 135 ( 8) 130 ( 6) 140 (7) Diastolic BP (mm Hg, SD) 80 ( 11) 84 ( 7) 82 ( 6) 87 (7) N events 275 (5%) 122 (4%) 153 (6%) BMIAU : AbbreviationlistsinTables1and2havebeenupdated:Pleasecheckandverifythatalladdedentriesarecorrectlyabbreviated: , body mass index; BP, blood pressure; CI, confidence interval; CVD, cardiovascular disease; SD, standard deviation. � Within the optimal respective bandwidths.…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…The density plots for diastolic BP, systolic BP, and the BPS are reported in Fig 1 . The graphical inspection of these plots confirmed the absence of manipulation around the respective cutoffs, since the density curve runs smoothly through the cutoff (if a manipulation had occurred, we would have seen a jump in the distribution of these variables close to the cutoff). The same result applies to the density plots for the reduced sample for the analysis of the secondary 18) 135 ( 8) 130 ( 6) 140 (7) Diastolic BP (mm Hg, SD) 80 ( 11) 84 ( 7) 82 ( 6) 87 (7) N events 275 (5%) 122 (4%) 153 (6%) BMIAU : AbbreviationlistsinTables1and2havebeenupdated:Pleasecheckandverifythatalladdedentriesarecorrectlyabbreviated: , body mass index; BP, blood pressure; CI, confidence interval; CVD, cardiovascular disease; SD, standard deviation. � Within the optimal respective bandwidths.…”
Section: Resultsmentioning
confidence: 67%
“…The current evidence on the effect of hypertension diagnosis differs from the evidence on the effect of the other abovementioned diseases because of the mixed nature of the results hitherto reported. Studies using an RD design in samples from China and South Africa have shown an significant decrease in BP 2 years after diagnosis [ 4 , 5 ] and a significant improvement in diet 3 to 4 years after diagnosis [ 6 , 7 ]. Conversely, studies on the US population have showed no improvement in dietary patterns after a diagnosis of hypertension within 2 years of diagnosis [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations